(untitled) (Research, Society and Development, 2020)
The injuries caused by firearms raise a great concern for public health and safety, which affects thousands of people every year, especially the military police, a public security agent who is daily exposed to the inherent risks in their profession fighting crime. In this context, the present study aimed to describe the of military police, profile in the service of the state of Pará injured by firearms and to identify their causes, locations and circumstances of the fact that occurred in the years 2017 to 2019 in the Metropolitan Region of Belém, Pará, Brazil. For this purpose, the statistical technique Exploratory Data Analysis was used and it was found that the majority of military police officers who were victims of crimes for firearm shot are male, military police lower rank, aged 42 to 49 years old they were off duty at the time of incident and hit in the lower limbs by murder attempted. Therefore, it is concluded that the risk in the police profession is constant. The firearms fired by the accused are usually intended to kill the police and when they do not kill, they leave not only marks of physical violence, but also possible mental health problems.